Ljubljansko barje - primernost za kmetijstvo - Ogorelec, Breda (Geografski vestnik, 1984)
In Slovenia, various methods of defining the physical potential for agriculture are used. Some of them are generally applied, others are adapted to individual characteristics of a certain region. Among the latter is the method described in the paper. Ljubljansko barje, a plain covering 16000 ha, lying in a humid climate and having a poor drainage, is a former lake that later turned into a swamp. During last few centuries, with help of hydromeliorations, it has changed into pastures, meadows and fields. Because of more or less regular floods and high watertable, hydromorphyc soils prevail. In the process of defining the physical potential for agriculture the following factors were used: soil types, occurence of floods, built-up areas, woods, water-reserves, botanical reserves, equisetum palustre. Some of the factors have excluded areas from further evaluation, others imposed certain limitations. The final result was a map (scale 1:25000) showing categories of potentialities for fields, meadows, or both, ranging from I to IV. High quality farming areas are limited to the edge of the Ljubljansko barje and they should be excluded from further urbanisation. Finally the relationship between agriculture and other users of space was described, showing that conflicts are scarce.
Keywords: geografija; infrastruktura; kmetijstvo; Ljubljansko barje; naravna dediščina; odlagališče odpadkov; poselitev; varstvo dediščine